INTERACTIVE MULTIMEDIA IN EFL CLASSROOM: A STUDY OF TEACHING READING COMPREHENSION AT JUNIOR HIGH SCHOOL IN INDONESIA - Nadirah, Nadirah; Asrifan, Andi; Vargheese, K. J.; Haedar, Haedar (Study Program of English Literature, 2020)
The objectives of the research were to find out: (1) whether or not the use of interactive multimedia improve students reading comprehension in the Eighth-Grade of SMP Negeri 4 Panca Rijang and (2) whether or not the use of interactive multimedia interest students’ in learning reading comprehension in the Eighth-Grade of SMP Negeri 4 Panca Rijang. This research employed mixed method design that applied experimental and control group. The population of the research was the Eighth-Grade students of SMP Negeri 4 Panca Rijang. The result of data analysis showed that there was significant difference between achievement of the students who used interactive multimedia and those who did not use interactive multimedia (conventional technique) in reading comprehension. It was proved by the mean score of experimental group was higher than control group in post-test (59.35 > 46.75). Furthermore, the result of the t-test value (3.581) was greater than t-table (α = 0.05; df = 38; t-table = 2.021) which means that H1 was accepted. The data analysis of questionnaire showed that the students had high interest toward the use of interactive multimedia in reading comprehension. It was supported by 4 students (20%) who were strongly interested, 14 students (70%) who were interested and 2 students (10%) who were moderate. The mean score of students’ answers in questionnaire (79.55) was classified as interested category. Based on the data analysis, the researcher concluded that: (1) the application of interactive multimedia enhanced the students’ ability in reading comprehension; (2) the application of interactive multimedia strategy in reading comprehension was interesting for the students.